Settlement of the Fulfillment of Wife and Child Livelihood by the Islamic Religious Council Southern Patani Region of Thailand - Darmawijaya, Edi; Ma'ming, Miss Maslinee (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Livelihood is all the needs and necessities that occur according to circumstances and places, such as food, clothing, shelter, assistance, and all his needs according to tradition because the law of subsistence is an obligation of a husband towards his wife and family. The Islamic Religious Council (MAIP) of Patani Region has a special working position namely Qadhi which handles matters related to family matters, in the Islamic Religious Council of Southern Patani Thailand does not have a Law or Compilation of Islamic Law (KHI) like Indonesia, but the responsible party will handle issues related to the family rights of Muslims by referring to the fiqh of Imam Shafi'i. In the case of non-fulfillment of the support of wives and children according to the religious assembly, for the Islamic religious assembly, there is no written fatwa, only a letter of agreement that can be an important asset in resolving the problem. This research uses qualitative methods, taking the background of informants, data collection is carried out using observation, interviews, and documentation. The results of this study concluded that after the marriage bond held a taklik letter (agreement) between husband and wife because it held a taklik made by the Islamic Religious Council (MAIP) so that the husband did not commit violence against his wife unfairly and followed shari'i, husbands who did not follow the taklik letter (Agreement) then the wife could complain to the Village Imam or the Islamic Religious Council (MAIP). The wife must bring two witnesses or concrete evidence, the Islamic Religious Council (MAIP) will give advice related to Islamic teachings that follow shari'a law so that peace arises between husband and wife then husband and wife may be added a taklik letter that has been determined by the Islamic Religious Council (MAIP) for the problem of not fulfilling income with the agreement between husband and wife, and the husband does not provide for himself, hurts and does not occupy the position for more than four months the wife may be fasahk